If you ask me [compact disc, unabridged] : (and of course you won't) - White, Betty, 1922- (Penguin Audio, 2011)
A personal account by the popular actress shares stories from her decades in Hollywood while offering her lighthearted perspectives on topics ranging from sex and aging to animal welfare and television.